Career Capital Development and Career Expectations of Self-Initiated Expatriates : Case of Finnish Self-Initiated Expatriates in Asia - Ruohotie, Heini (My University, 2026)
Globalization has significantly transformed career paths and workforce mobility, and inter-national work experience has become one of the most central competitive advantages in today's labor market. Today, self-initiated expatriates, who move abroad to work without organizational support, make up the majority of the global expatriate population and are therefore a significant yet understudied group. In particular, Western expatriates working in Asia and their career capital have received little attention in research, despite Asia's growing economic importance having made it an attractive destination for many self-initiated expatriates. Addressing this research gap, the aim of this thesis is to examine what type of career capital Finnish self-initiated expatriates develop in Asia, and how they expect the acquired career capital to impact their future career development. The theo-retical framework of the thesis is DeFillippi and Arthur's (1994) career capital theory. The study was conducted as qualitative research, and the data was collected using semi-structured in-depth interviews. The sample consisted of six Finnish self-initiated expatri-ates who worked or had previously worked in Asia. The in-depth interviews focused on the participants' experiences of career capital development in Asia and their expectations on how the acquired career capital would impact their future career development. The analysis was conducted based on the three ways of knowing of the selected theoretical framework: knowing-how, knowing-why and knowing-whom. The findings suggest that Finnish self-initiated expatriates develop significant career capital across all three ways of knowing. Knowing-how developed in a culturally demanding environment, enhancing the participants' cross-cultural communication skills and broad Asia-specific business knowledge. Knowing-why deepened, strengthening the participants' professional identity. Knowing-whom, while the most challenging of the developed dimensions, was reflected in the participants' extensive multicultural networks. The most unexpected finding was the value of Finnish identity as a form of knowing-why that activated as a professional as-set in Asia. Furthermore, the sample consisting of long-term self-initiated expatriates demonstrated more positive career trajectories than prior research would suggest. Re-garding future career expectations, the participants considered the career capital they had accumulated to be valuable particularly in external labor markets, but were pessimis-tic about how the value of their career capital would be understood in Finland. The study extends the research on career capital theory by applying it to a previously un-derstudied context. From a practical perspective, it also highlights the gap between the career capital accumulated by Finnish self-initiated expatriates in Asia and Finnish em-ployers' ability to recognize it. Finally, the study offers perspectives for further research taking into account the limitations of the study.

Globalisaatio on muuttanut merkittävästi työuria ja työvoiman liikkuvuutta, ja kansainväli-sestä työkokemuksesta onkin tullut yksi keskeisimmistä kilpailuvalteista nykypäivän työ-markkinoilla. Tänä päivänä oma-aloitteiset ekspatriaatit, jotka muuttavat ulkomaille työn perässä ilman organisaation tukea, muodostavat enemmistön maailman ekspatriaattipopu-laatiosta ja ovat siten keskeinen, mutta vähän tutkittu, väestöryhmä. Erityisesti Aasiassa työskenteleviä länsimaalaisia ekspatriaatteja ja heidän urapääomaansa ei ole juuri tutkittu, vaikka Aasian kasvava taloudellinen merkitys on tehnyt siitä houkuttelevan kohteen monil-le oma-aloitteisille ekspatriaateille. Tutkimusaukkoon vastaten tutkielman tavoitteena on tarkastella millaista urapääomaa suomalaiset oma-aloitteiset ekspatriaatit kehittävät Aasi-assa ja miten he odottavat sen vaikuttavan heidän tulevaan urakehitykseensä. Tutkielman teoreettisena viitekehyksenä toimii DeFillippin ja Arthurin (1994) urapääomateoria. Tutkimus toteutettiin kvalitatiivisena tutkimuksena ja tutkimusaineisto kerättiin puo-listrukturoituja syvähaastatteluja hyödyntäen. Syvähaastatteluihin osallistui kuusi suoma-laista oma-aloitteista ekspatriaattia, jotka työskentelivät tai olivat työskennelleet eripuolil-la Aasiaa. Haastatteluissa keskityttiin osallistujien kokemuksiin urapääoman kehittymisestä Aasiassa ja heidän odotuksiinsa urapääoman vaikutuksista tulevaan urakehitykseen. Analyysi tehtiin valitun teoreettisen viitekehyksen kolmen tietämisen tavan, miten-tietämys, miksi-tietämys ja ketä-tietämys, pohjalta. Tutkimustulokset osoittavat, että suomalaiset oma-aloitteiset ekspatriaatit kehittävät merkittävää urapääomaa kaikilla kolmella osa-alueella. Miten-tietämys kehittyi kulttuurillisesti vaativassa ympäristössä osallistujien kulttuurienvä-lisiä viestintätaitoja ja laajaa Aasia-osaamista. Miksi-tietämys syveni vahvistaen muun muas-sa osallistujien ammatillista identiteettiä. Ketä-tietämys, vaikka kehitetyistä ulottuvuuksis-ta haasteellisin, näkyi osallistujien laajoina monikulttuurisina verkostoina. Odottamattomin havainto oli suomalaisen identiteetin arvo miksi-tietämyksen muotona, joka aktivoitui ammatillisena vahvuutena Aasiassa. Lisäksi pitkäaikaisista oma-aloitteisista ekspatriaateista koostuva otos osoitti positiivisempia urakehityskulkuja kuin aiemmat tutkimukset antavat ymmärtää. Tulevaisuuden uraodotusten osalta osallistujat arvioivat kerryttämänsä urapää-oman arvokkaaksi kansainvälisillä työmarkkinoilla, mutta suhtautuivat pessimistisesti sii-hen, miten heidän urapääomansa arvo ymmärrettäisiin Suomessa. Tutkimus laajentaa tutkimusta urapääomateoriasta soveltamalla sitä aiemmin vähän tutkit-tuun kontekstiin. Käytännössä se tuo esiin kuilun oma-aloitteisten ekspatriaattien kerty-neen urapääoman ja suomalaisten työnantajien kyvyn tunnistaa kertynyt urapääoma välillä. Lopuksi tutkimus tarjoaa näkökulmia jatkotutkimukselle ottaen huomioon tutkimuksen rajoitukset.
Keywords: expatriates; expatriate Finns; career development; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business